Characterization of the complete chloroplast genome and phylogenetic analysis of Silene jenisseensis (Caryophyllaceae). Issue 1 (2nd January 2020) - Ling, Li-Zhen
Abstract: The first complete chloroplast genome (cp) sequences of Silene jenisseensis were reported in this study. The S. jenisseensis cp genome was 150, 299 bp in size, with two inverted repeat (IR) regions of 25, 384 bp, the large single-copy (LSC) region of 82, 153 bp, and the small single-copy (SSC) region of 17, 378 bp. The cp genome of this species contained 111 genes, including 77 protein-coding genes, 4 ribosomal RNA, and 30 transfer RNA genes. The overall GC content was 36.4%. Phylogenetic analysis of the cp genomes within the Caryophyllaceae family suggests that S. jenisseensis is closer to the clade formed by S. capitata and S. aprica .